Limited Open Reduction and Transepiphyseal Intramedullary Kirschner Wire Fixation for Treatment of Irreducible Distal Radius Diaphyseal Metaphyseal Junction Fracture in Older Children - Wang, Rufa; Wu, Liwei; Wang, Yinming; Fan, Minjie; Wang, Yiwei; Ning, Bo; Zheng, Pengfei (Frontiers in Pediatrics, 2022)
Objective: This study aimed to compare limited open reduction and transepiphyseal intramedullary fixation with Kirschner wire (LOR-TIKW) versus open reduction and internal fixation with plate and screw (ORIF-PS) for treatment of irreducible distal radius diaphyseal–metaphyseal junction (DMJ) fracture in older children. Methods: Data of children (aged 10-14 years) treated in our hospital for distal radius DMJ fractures with LOR-TIKW or ORIF-PS from January 2018 to December 2019 were retrospectively analyzed. Follow-up was until radiographic union. Demographic, clinical, and radiographic data; treatment cost; healing time; functional outcome (by Price criteria); complications; and postoperative angulation and displacement were compared between children treated by the two methods. Statistical analysis was performed with alpha set at P < 0.05. Results: A total of 26 children were included: 14 treated with LOR-TIKW and 12 with ORIF-PS. Operation time was less (22.1 min vs. 46.7 min, P < 0.0001), surgical incision smaller (2.43 cm vs. 5.00 cm, P < 0.0001), cost of internal fixation lower (US$, 40.6 vs. 2020, P < 0.0001), and healing time shorter (4.79 weeks vs. 5.64 weeks, P = 0.03) with LOR-TIKW; however, postoperative fracture angulation was slightly larger (1.07° vs. 0.83°, P = 0.85) and displacement slightly more (0.86 mm vs. 0.58 mm, P = 0.44) in the LOR-TIKW group. Rate of union, functional outcome, and complications were not significantly different between the groups. Conclusion: For irreducible DMJ fracture of distal radius in older children, LOR-TIKW appears to be a promising method with several advantages over ORIF-PS.